PEMANFAATAN LIMBAH KERTAS KORAN UNTUK PEMBUATAN PANEL PAPERCRETE - Gunarto, Arief; Satyarno, Iman; Tjokrodimuljo, Kardiyono (Civil Engineering Forum Teknik Sipil, 2008)
The availability of natured material for construction is so limited and in the other hand it’s demand increase. The consequence is try to explore alternative materials such as waste material which has not been explored as construction material. The recycled paper were chosen to be used as a filler component and mixed with cements as a bonding agent. Hence paper fiber include other paper ingredients will become construction material and at the same time to minimized the impact of waste paper to environment. One of the way to enhanced the paper and cements mixture quality as a component of concrete panel were by adding an admixture. Cements and water mixture are the bonding agent, while the filler material are paper and sugar cane admixture as the retarder. This mixture can be categorized as a light concrete. If it used as a papercrete panel will be the alternative building element to reduc dead load for the main structures. A light concrete panel from a mixture of news paper powder and white cement as a bonding agent, forms panel through cold pressed process. Papercrete panel and cube are made for sample with size 420 x 420 x 7 mm³ and 50 x 50 x 50 mm³ respectively. The volume ratio of paper - cements mixture were 2, 3, 4, are made of two condition i.e. without admixtures and with 0,2% sugar cane admixtures concentration by cement weight. The research will find out papercrete unit weight, flexural strength panel, cubical compressive strength, modulus of elasticity, water absorption and the price of concrete panel at every cubic and square meter. The result is concrete unit weight ranges from 840 - 933 kg/m³, the highest flexural strength papercrete panel reached at volume ratio of paper - cements mixture 2 with sugar admixture was 8,36 MPa. The highest the compressive strength reached at the volume ratio of paper – cements mixture 2 with sugar cane admixture was 2,48 MPa. The highest modulus of elasticity at the volume ratio of paper - cements mixture 3 with sugar admixture was 6,48 MPa with water absorption still above 50%. that is lower water absorption 56,93% at volume ratio of paper - cements mixture 2 with sugar cane admixture and the highest absorption at volume ratio of paper - cements mixture 4 was 84,23%. While the increasing of paper powder in mixture, concrete unit weight, flexural strenth, compressive strength and modulus of elasticity papercrete becoming lower with the increasing of water absorption. Addition of sugar cane 0,2% by cements weight haves an flexural strength improvement up to 7,66%, and enhanced compressive strength 50,24%, improvement concrete weight equal to 4,71% and reduced adsorption until 10,7%, but in papercrete product with sugar cane admixture doesn't have significant effect of production budget.